(untitled) (World Science, 2020)
The article proposes to consider the possibilities of lean production technologies (lin-technologies) in educational organizations. The authors conclude that the use of lean production can achieve high results in solving a number of important tasks and provide a favorable innovation environment for the creation and implementation of innovative projects that are a priority in modern education.